2016
DOI: 10.3390/md14100177
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroisocoumarins from the Mangrove-Derived Fungus Penicillium citrinum

Abstract: Three new dihydroisocoumarin penicimarins G–I (1–3), together with one known dihydroisocoumarin (4) and three known meroterpenoids (5–7), were obtained from a fungus Penicillium citrinum isolated from the mangrove Bruguiera sexangula var. rhynchopetala collected in the South China Sea. Their structures were elucidated by the detailed analysis of spectroscopic data. The absolute configuration of 1 was determined by the X-ray diffraction analysis using Cu Kα radiation. The absolute configurations of 2 and 3 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 21 publications
(27 reference statements)
2
35
0
Order By: Relevance
“…Phomasatin (141) showed no cytotoxicity (IC 50 > 50 µM) against Molm 1, HL-60, and PC-3 cell lines using MTT assay [84]. Compounds 154 and 155 had no cytotoxic potential against HeLa, MCF-7, and A549 cells (IC 50 > 50 µM) [56]. Compounds 157-159, dihydroisocoumarin derivatives reported from Penicillium simplicissimum were examined against Artemia salina (brine shrimp lethality).…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…Phomasatin (141) showed no cytotoxicity (IC 50 > 50 µM) against Molm 1, HL-60, and PC-3 cell lines using MTT assay [84]. Compounds 154 and 155 had no cytotoxic potential against HeLa, MCF-7, and A549 cells (IC 50 > 50 µM) [56]. Compounds 157-159, dihydroisocoumarin derivatives reported from Penicillium simplicissimum were examined against Artemia salina (brine shrimp lethality).…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…In our ongoing research on mangrove-derived fungi, we have found some new bioactive metabolites (including metabolites with inhibitory activity against α-glucosidase) [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A mangrove-derived fungus Daldinia eschscholtzii HJ004 attracted our attention due to the inhibitory activity against α-glucosidase of its EtOAc extract, and three polyketide derivatives with strong inhibitory activity against α-glucosidase have been isolated [9]. A further chemical investigation of the fermentation broth resulted in the identification of two new polyketides 8-O-methylnodulisporin F (1) [15] and nodulisporin H (2) [15], two new naphthoquinones 5-hydroxy-2-methoxy-6,7-dimethyl-1,4-naphthoquinone (3), and 5-hydroxy-2-methoxynaphtho [9-c]furan-1,4-dione (4), and a new naphthofuran 1,3,8-trimethoxynaphtho [9-c] furan (5), together with five known compounds, 4-O-methyl eleutherol (6) [16], 2-acetyl-7-methoxybenzofuran (7) [17], (-)-orthosporin (8) [18], diaporthin (9) [18], and 6-hydroxymellein (10) [19] (Figure 1). The electronic circular dichroism (ECD) calculation method was used to establish the absolute configurations of the stereogenic carbons in 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our search for new bioactive compounds from fungal sources [6,8,9], the fungus Penicillium sp. JY246 was isolated from the mangrove's stem Ceriops tagal, collected from the South China Sea.…”
Section: Introductionmentioning
confidence: 99%